A multi-country analysis of multidimensional poverty in contexts of forced displacement - Admasu, Y; Alkire, S; Ekhator-Mobayode, UE; Kovesdi, F; Santamaria, J; Scharlin-Pettee, S (World Bank, 2021)
Despite the many simultaneous deprivations faced by forcibly displaced communities, such as food insecurity, inadequate housing, or lack of access to education, there is little research on the level and composition of multi- dimensional poverty among them, and how it might differ from that of host communities. Relying on house- hold survey data from selected areas of Ethiopia, Nigeria, Somalia, South Sudan, and Sudan, this paper proposes a Multidimensional Poverty Index (MPI) that captures the overlapping deprivations experienced by poor individuals in contexts of displacement. Using the MPI, the paper presents multi-country descriptive analysis to explore the relationships between multidimensional poverty, displacement status, and gender of the household head. The results reveal significant differences across displaced and host communities in all countries except Nigeria. In Ethiopia, South Sudan, and Sudan, female-headed households have higher MPIs, while in Somalia, those living in male-headed house- holds are more likely to be identified as multidimensionally poor. Lastly, the paper examines mismatches and overlaps in the identification of the poor by the MPI and the $1.90/ day poverty line, confirming the need for complementary measures when assessing deprivations among people in con- texts of displacement.